Local fat content and muscle quality measured by a new electrical impedance myography device: correlations with ultrasound variables. Issue 3 (4th March 2021) - Longo, Stefano; Coratella, Giuseppe; Rampichini, Susanna; Borrelli, Marta; Scurati, Raffaele; Limonta, Eloisa; Cè, Emiliano; Esposito, Fabio
Abstract : The present study investigated the relationship between local fat percentage (SKfat ) and muscle quality (MQ) estimated by a new hand-held electrical impedance myography ( h EIM) device or derived from ultrasound and strength assessments. The right anterior thigh of 90 healthy participants (mean ± SD; age=22.9 ± 2.9 years; 45 men: BMI = 23.9 ± 2.4 kgm −2 ; 45 women: BMI = 21.1 ± 1.9 kgm −2 ) was scanned by h EIM and ultrasound. Correlations between SKfat, local subcutaneous fat (SUBfat ), and echo intensity (EIus ) were explored. Correlations between MQ, EIus, quadriceps femoris anatomical cross-sectional area (ACSAQF ), knee extensors maximum voluntary isometric torque (T), T/ACSAQF, EIus /SUBfat, and ACSAQF /SUBfat were also assessed. SKfat correlated with SUBfat ( r = 0.88; p < 0.001) and EIus ( r = 0.64; p < 0.001). MQ correlated with EIus ( r = −0.66; p < 0.001), ACSAQF ( r = 0.37; p < 0.001), EIus /SUBfat ( r = 0.37; p < 0.001), and ACSAQF /SUBfat ( r = 0.81; p < 0.001). Multiple regression analysis showed that SUBfat, EIus, and sex explained 86% of SKfat variance, whereas ACSAQF /SUBfat, sex and EIus explained 75% of MQ variance. In conclusion, high h EIM local fat percentage relates to greater subcutaneous fat and intramuscular non-contractile tissue content. High h EIM muscle quality relates to greater muscle-size:subcutaneous-fat ratio and contractile tissue content. Sex influences the prediction of both parameters. This h EIM device seems to be useful to estimate local thigh composition.